Characterisation of cardiac pathology in 23 autopsies of lethal COVID‐19 - Jasmin D Haslbauer; Alexandar Tzankov; Kirsten D Mertz; Nathalie Schwab; Ronny Nienhold; Raphael Twerenbold; Gregor Leibundgut; Anna K Stalder; Matthias Matter; Katharina Glatz (Wiley, 2021)
Abstract While coronavirus disease 2019 (COVID‐19) primarily affects the respiratory tract, pathophysiological changes of the cardiovascular system remain to be elucidated. We performed a retrospective cardiopathological analysis of the heart and vasculature from 23 autopsies of COVID‐19 patients, comparing the findings with control tissue. Myocardium from autopsies of COVID‐19 patients was categorised into severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) positive (n = 14) or negative (n = 9) based on the presence of viral RNA as determined by reverse transcriptase polymerase chain reaction (RT‐PCR). Control tissue was selected from autopsies without COVID‐19 (n = 10) with similar clinical sequelae. Histological characteristics were scored by ordinal and/or categorical grading. Five RT‐PCR‐positive cases underwent in situ hybridisation (ISH) for SARS‐CoV‐2. Patients with lethal COVID‐19 infection were mostly male (78%) and had a high incidence of hypertension (91%), coronary artery disease (61%), and diabetes mellitus (48%). Patients with positive myocardial RT‐PCR died earlier after hospital admission (5 versus 12 days, p < 0.001) than patients with negative RT‐PCR. An increased severity of fibrin deposition, capillary dilatation, and microhaemorrhage was observed in RT‐PCR‐positive myocardium than in negatives and controls, with a positive correlation amongst these factors All cases with increased cardioinflammatory infiltrate, without myocyte necrosis (n = 4) or with myocarditis (n = 1), were RT‐PCR negative. ISH revealed positivity of viral RNA in interstitial cells. Myocardial capillary dilatation, fibrin deposition, and microhaemorrhage may be the histomorphological correlate of COVID‐19‐associated coagulopathy. Increased cardioinflammation including one case of myocarditis was only detected in RT‐PCR‐negative hearts with significantly longer hospitalisation time. This may imply a secondary immunological response warranting further characterisation.